The difference between gender in terms of nomophobia in Turkey: a meta-analysis - Avcı, Esin (The European Research Journal, 2022)
Objectives: Technology unfortunately even though making our life easier, causes a lot of psychological problems when it is not used reasonably. One of them is the inability to live without a smartphone: nomophobia. This meta-analysis study considered nomophobia in Turkey in terms of gender. Methods: Using “nomophobia”, “Nomophobia Scale “, “Nomophobia Questionnaire (NMP-Q)”, “NMP-Q”and “smartphone” keywords, 9 electronic bibliographic databases, reference lists of relevant studies, and searches of the internet were performed to identify articles related to the nomophobia scale. The inclusion criteria were studies that the nomophobia questionnaire (NMP-Q) utilized to Turkish people, published in English or Turkish, and report the questionnaire score by mean/standard deviation according to gender. The mean age and sample size ratio, which were thought to have an effect on heterogeneity, are analyzed by meta-regression. Results: A total of 3370 studies were located, with 10 meeting the inclusion criteria. It revealed that females are found to be more nomofobic than males according to Nomophobia Questionnaire (NMP-Q). Conclusions: Most of the studies discussed in this study were applied to student groups. Applying nomophobia studies to different sample groups is important in determining the prevalence of nomophobia in the population and taking precautions.